The Normalisation of Portuguese-Chinese Relations and Macao’s Handover to Mainland China, 1974-79 - Fernandes, Moisés Silva (2017)
Although many people believe that small or medium powers tend to be very concerned with overseas territories, this was not true in the case of Macao. The great power, mainland China, showed very little interest in foreign affairs, because it knew that the outcome of the handover would be in its favour. Nonetheless, from May 1974 to July 1975, both China and Portugal had to demarcate their positions. The Portuguese entered into informal conversations with the Chinese ambassador to France, Zeng Tao, in August 1975, which lasted until January 1978, a total of almost three years. As soon as power in mainland China shifted from the leftists to the moderates, however, the new ambassador in Paris, Han Kehua, made it clear that he wanted things settled in six months. However, in 1978, the Portuguese cabinet had three different prime ministers and three different ministers of foreign affairs. Ultimately, the Portuguese cabinet had to give in to mainland China, on 8 February 1979.